Evaluation of the Flanagan Quality of Life Scale for older adults - Souza, Luciana Bronzi de [UNESP]; Corrente, José Eduardo [UNESP] (My University, 2013)
Purpose: to evaluate the Flanagan Quality of Life Scale applied in a representative sample of urban older people population of Botucatu city, São Paulo, Brazil. Methods: a cross-sectional study was carried out with a representative sample of 365 older people obtained considering a prevalence of 50% of satisfaction with the quality of life, 95% of reliability and an 5% error margin. Descriptive analyzes were initially made for sociodemographic data and associations with quality of life. To obtain the domains of the Flanagan Quality of Life Scale, a factor analysis was running extracting the principal components using the varimax rotation. Results: 361 older people were included and the average age participants was 72.10 (SD= 7.35) years. The majority were female, married with low education level. The income varied from none to 8.253,50 U.S. dollars, approximately. The mean score of the questions of the Flanagan Quality of Life Score was 84.76, indicating a good quality of life. The reliability coefficient Cronbach's α was 0.81, demonstrating the efficiency of the instrument. After a factorial analysis, the domains considered by the older adults as the most important to their quality of life agree with those proposed by Flanagan. Conclusion: The Flanagan Quality of Life Scale as described initially proved to be an efficient and reliable tool to assess the quality of life of older adults.